(2x+4)(3x-3)=0

Simple and best practice solution for (2x+4)(3x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+4)(3x-3)=0 equation:


Simplifying
(2x + 4)(3x + -3) = 0

Reorder the terms:
(4 + 2x)(3x + -3) = 0

Reorder the terms:
(4 + 2x)(-3 + 3x) = 0

Multiply (4 + 2x) * (-3 + 3x)
(4(-3 + 3x) + 2x * (-3 + 3x)) = 0
((-3 * 4 + 3x * 4) + 2x * (-3 + 3x)) = 0
((-12 + 12x) + 2x * (-3 + 3x)) = 0
(-12 + 12x + (-3 * 2x + 3x * 2x)) = 0
(-12 + 12x + (-6x + 6x2)) = 0

Combine like terms: 12x + -6x = 6x
(-12 + 6x + 6x2) = 0

Solving
-12 + 6x + 6x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '6'.
6(-2 + x + x2) = 0

Factor a trinomial.
6((-2 + -1x)(1 + -1x)) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2

Subproblem 2

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Solution

x = {-2, 1}

See similar equations:

| x-2.4=5.6 | | 3x^3+87x^2+162x=0 | | 5x+1-18= | | (7x+15)+(x+5)=180 | | .25(8-6x+12)= | | 15a^2-8=29a+9 | | 2x^3-21x^2+34x=0 | | 8x^3-3x^2-32x+12=0 | | 10+3x+2x=-45 | | 9+2y=y | | 9(x-1)=6(x+5) | | (3+w)w=w(7-w) | | 5j-j=12 | | x^2-50x+100=8400 | | 6x^3+26x^2-76x=0 | | 9-(w+4)=-10 | | 2x-6-2(2x+8)3=4x+1 | | 3.5x=9 | | .1x-.9x^2=0 | | X^2+24x=172 | | 8=4+4 | | -5(5p+2)-49=3(3p+3) | | 8x^3-3x^2=32x-12 | | 5f-15=2f-3 | | d/dx(9x/8) | | (x-1)(5x+2)=-13(x-1) | | 3x/4-x=x/10-5/2 | | 4x-3+43=180 | | 28p^2-108p-14=2 | | -4x^3-40x^2-64x=0 | | 5(x-2)+(-9)=7(1-x) | | 64=lw |

Equations solver categories